Pyrolysis of torrefied biomass: Optimization of process parameters using response surface methodology, characterization, and comparison of properties of pyrolysis oil from raw biomass - Singh S.; Chakraborty J.P.; Mondal M.K. (My University, 2025)
Pyrolysis of torrefied Acacia nilotica was investigated in a tubular fixed-bed reactor under nitrogen environment. The process was optimized using response surface methodology coupled with central composite design, in order to obtain the maximum yield of pyrolysis oil. The maximum yield of pyrolysis oil (33.59 wt %) was obtained at 507.04 °C, retention time of 58.25 min, heating rate of 38.00 °C/min, and sweeping gas flow rate of 40.52 mL/min. Analysis of variance confirmed that pyrolysis of torrefied biomass for maximum pyrolysis oil yield highly depended on temperature followed by heating rate, retention time, and sweeping gas flow rate, respectively. Pyrolysis of raw biomass was also carried out at the optimum condition for comparing the quality of both pyrolysis oils. The pyrolysis oil samples were subjected to FTIR, GC-MS, and 13C NMR analyses along with estimation of water content, pH, viscosity, HHV, etc., for comparing the physicochemical characteristics. Results showed that total aromatic carbon, carbonyl carbon, and primary alkyl carbon of pyrolysis oil from torrefied biomass increased by 40.28, 51.36, and 6.34%, respectively, as compared to pyrolysis oil from raw biomass. The phenol derivative compounds are increased by 18.91%. The HHV and pH of pyrolysis oil from torrefied biomass increased by 23.53, 42.15%, respectively, while water content decreased by 34.37% as compared to pyrolysis oil from raw biomass. Thus, with rapid advancement in pyrolysis process, the integrated approach of torrefaction-pyrolysis process may be beneficial to produce cleaner pyrolysis oil as compare to raw biomass. © 2020 Elsevier Ltd